2009
DOI: 10.1097/wad.0b013e318199d833
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical Features With Argyrophilic Grains at Autopsy

Abstract: Argyrophilic grains (AGs) are a pathologic feature found in association with neurodegenerative disease. Some have suggested that these features may occur as a distinctive condition. We reviewed 80 subjects from our tissue bank with pathologically confirmed AGs and identified their clinical features. We compared these subjects' features to the features of subjects with matched clinical diagnoses but without AGs. Subjects with AGs represented 21.7% of the entire autopsy sample from 1999 through 2005 (80/367). Of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 37 publications
(40 citation statements)
references
References 26 publications
3
34
1
2
Order By: Relevance
“…One study found that argyrophilic grain disease was a common feature of PDD; 99 however, it did not seem to correlate well with PDD in two large autopsy series. 22, 75 TDP-43 inclusions, which are characteristic of frontotemporal lobar degeneration and amyotrophic lateral sclerosis, have also been found in limbic regions in a small number of PD and PDD patients, 100 but they do not seem to influence the outcome of dementia in PD.…”
Section: Neuropathology Underlying Pddmentioning
confidence: 94%
“…One study found that argyrophilic grain disease was a common feature of PDD; 99 however, it did not seem to correlate well with PDD in two large autopsy series. 22, 75 TDP-43 inclusions, which are characteristic of frontotemporal lobar degeneration and amyotrophic lateral sclerosis, have also been found in limbic regions in a small number of PD and PDD patients, 100 but they do not seem to influence the outcome of dementia in PD.…”
Section: Neuropathology Underlying Pddmentioning
confidence: 94%
“…Cerebral amyloid angiopathy (CAA) was defined semi-quantitatively with three levels of severity by analogy to the CERAD templates; for this study, significant CAA was defined when one or more cerebral lobes had a severity score of 2 or higher. Argyrophilic grains (Arg) were defined as typical spindle-shaped structures revealed by the Gallyas silver stain (26, 27) and were recorded as being present or absent.…”
Section: Methodsmentioning
confidence: 99%
“…Also commonly seen in brains from individuals of advanced age are tau-immunoreactive argyrophilic grains. However, argyrophilic grain disease is a 4R tauopathy featuring CA2 pretangles and dentate granule cell involvement, all acetylated tau-negative, none of these features are seen in AD/PART [54, 71, 84, 107, 120, 136, 138]. …”
Section: Differentiating Part From Other Neurodegenerative Diseasesmentioning
confidence: 99%